Investigating intrauterine exposure to methamphetamine on serine-threonine kinase pathway in male rat testis: METH effects serine-threonine kinase in spermatogenesis - Danesh Pasand, Sina; Zare, Nayere; Baghi Zadeh, Zahra; Ghorbani Yekta, Batool (Cellular and Molecular Biology, 2025)
Today, methamphetamine (METH) is being used by adolescents and young adults. Our previous research demonstrated that intrauterine exposure to METH induces apoptosis in testicles and seminiferous tubes. However, based on available literature, the mechanism of this effect remains unidentified. This study aimed to investigate proteins involved in sperm growth and development pathways, such as testis-specific serine/threonine kinases (TSSK) and receptor-interacting protein kinases 2 (RIPK2), and to study the serine-threonine kinase pathway in the testes of rats whose mothers received intraperitoneal METH during pregnancy. In the present study, female rats during pregnancy received either 5 or 10 mg/kg of METH or normal saline for ten days. After reaching maturity, their testes were isolated and examined for histopathological and immunohistochemical mechanisms. Results were analyzed and reported using statistical software. Results revealed that following intrauterine exposure to METH, TSSK protein expression reduced from 52.68±2.4% in the control group to 48.04±2.29% in the 2 mg/kg/day group and 12.83±3.35% in the 5 mg/kg/day group with P=0.0029 and F=72.63. In addition, RIPK2 protein expression increased from 8.34±2.69% in the control group to 31.17±3.69% in the 2 mg/kg/day group and 98.49±4.66% in the 5 mg/kg/day group, with p=0.0037 and F=61.14. Histopathological findings indicated a reduction in the thickness of germ layers following intrauterine exposure to METH, with the seminiferous tubule’s thickness decreasing. Inflammatory cell populations increased, and the number of vessels decreased due to intrauterine exposure to METH. Our study suggests intrauterine exposure to METH increases the prevalence of inflammatory cell populations, enhances RIPK2 protein expression, reduces the number of vessels, reduces the diameter of seminiferous tubes, decreases TSSK protein expression, and reduces the thickness of germ layers in testicular tissue. Apoptosis of spermatid cells observed in our previous study may be related to the signaling pathways of TSSK and RIPK2 proteins.